PENGARUH BERBAGAI KOMPOSISI LIMBAH PERTANIAN TERHADAP KADAR AIR, ABU, DAN SERAT KASAR PADA WAFER - Silvia Wulandari; Farida Fathul; Liman . (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
This experiment aims to know water content, ash, and crude fiber of wafer of various agricultural as feed and to know the best water content, ash, and crude fiber from wafer of various composition of agricutural waste. This experiment was held Juny-July 2014 in Bandar Baru Village Sukau Subdistrick West Lampung Regency. This sample were analyzed in the Laboratory of Animal Nutrition and Feed Science, Department of Animal Husbandry, Lampung University. The experimental design used in this research was Completely Randomized Design (CRD) with three treatments and four replications. The treatments were : A: sweet potato 8% + potato 3% + leaf couliflower 5% + china cabbage 10% + carrot 50% + chayote 5% + tomato 15,99 % + molasses 3% + salt 0,01%; B: sweet potato 15% + potato 5% + leaf couliflower 10% + china cabbage 15% + carrot 40% + chayote 6% + tomato 5,99 % + molasses 3% + salt 0,01%; C: sweet potato 20% + potato 7% + leaf couliflower 15% + china cabbage 20% + carrot 23% + chayote 8% + tomato 3,99 % + molasses 3% + salt 0,01%. The data were analyzed by using variance analysis with significant level of 5% and or 1%, and will be followed by the Least Significant Difference test (LSD). The results of this study showed that the composition of wafer with various agricultural wastes was not significant effect (P> 0.05) on water content, but significantly (P <0.05) of the crude fiber content and highly significant (P <0.01) against of the ash content. The best treatment on the wafer with various agricultural waste composition is wafer C (Keywords : Wafer, Agricultural Waste , Water Content, Ash Content, Crude Fiber Content)